PAP SMEAR, AN IMPORTANT SCREENING TOOL TO DETECT PRECANCEROUS STAGE OF CARCINOMA OF CERVIX - Haider, Gulfareen; Parveen, Zahida; Anjum, Farhana; Munir, Aftab (Journal of Ayub Medical College Abbottabad, 2013)
Background: Many women can be saved from carcinoma of cervix by detecting and treating its precancerous stage. Pap smear is cheap and easily available in majority of institutes. The objective of this study is to determine the frequency of abnormal Pap smear and role of Pap smear in detecting precancerous stage of cancer cervix in women. Methods: This is retrospective descriptive study was conducted in gynaecology outpatient department of Isra University Hospital, Hyderabad, Sind from Nov 2006 to Oct 2009. All women who presented in OPD with gynaecological complaints were included in the study. Pregnant women were excluded from the study. Smear was collected with an Aryes spatula and relevant information was obtained from the patient’s record and recorded on pre-designed Performa. Slides were then sent to pathology department. Data were analysed through SPSS-15 and presented as frequency and percentage. Results: Total 981 women underwent Pap smear screening. Majority (63.3%) of the patients belonged to age group of 31-40 years. One hundred and eighty (18.34%) smears were normal and 792 (80.7%) were abnormal. Among these abnormal smears, 739 (75.33%) smears were inflammatory while 4 (0.40%) women had Ca in situ and 4 (0.40%) had squamous cell carcinoma. Conclusion. Pap smear is an important screening tool to detect precancerous stage of carcinoma of cervix. It should be done periodically in all married and high risk women for early detection of a precancerous stage. Keywords: Pap smear, inflammatory, cancer cervix, malignancy, gynaecological tumour, diagnosis